Quine versus Davidson : truth, reference, and meaning - Kemp, Gary, 1960 Oct. 15- (Oxford : Oxford University Press, 2012)
Gary Kemp presents a penetrating investigation of key issues in the philosophy of language, by means of a comparative study of two great figures of late 20th century philosophy. He reveals unexplored tensions between the views of Quine and Davidson, and presents a powerful argument in favour of Quine and methodological naturalism.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Quine, W. V; Davidson, Donald, -- 1917-2003.; Language and languages -- Philosophy